noi-loro. Storia e attualità della relazione educativa fra adulti e bambini - BANDINI, GIANFRANCO (Strumenti per la didattica e la ricerca, 2010)
The idea behind this book - devoted to the relations between adults and children - emerged within a specific educational experience launched in an experimental manner in 2006 by the faculty of educational science of Florence University and now in its fourth edition. These are teaching courses held in the evening and on Saturdays to make it easier for students with daytime jobs to attend the lessons. The quest for new forms of organisation was accompanied by a meditation on teaching, which brought out several very interesting educational themes which were effectively transversal to the various disciplines. This book presents the results of this methodological approach, aimed at fostering a conscious, reflective and personal learning. As the title suggests, the essays are designed to focus the question of the educational relationship within a multidisciplinary perspective. Us-them, to remind ourselves that adults have a fundamental and inescapable responsibility. The relationship is typically asymmetrical, with special features and decidedly variable over time. It has in fact been marked for centuries by a failure to recognise the needs of the youngsters and their own subjectivity, to the point of arriving at disturbing levels of violence and coercion. Such cases have been justly referred to a 'black pedagogy', which sadly is far from being everywhere a thing of the past, and even in Italy has left deep and persistent traces. For these reasons the study of the educational relationship has numerous relevant aspects of interest, all extremely topical, and represents a fundamental argument that adults must consciously address. Educators and teachers, parents and students, can all thus enhance their sensitivity and competence with a view to consolidating the reflective practices that are now considered absolutely indispensable for those who live in contact with children and adolescents.